Carton Coon’s Riddle: Anthropologist, Archaeologist, or CIA Agent? (Critical Review of Carlton Stevens Coon’s Methodology and Publications in the Iranian Paleolithic Archaeology) - Hamed Vahdati Nasab (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Carlton Stevens Coon is one of the most prominent figures in the Prehistoric Archaeology of Iran. He conducted the first systematic field expeditions in the Iranian Archaeology 70 years ago. For many years his works have been taught in the Iranian universities. Now and after almost seventy years, a need for critical review of his works sounds inevitable. In this research, such review was performed based on five categories: theoretical approaches of the field works, degree of specialty, fieldwork approaches, data collecting methods, and data processing procedures. The results indicate that his theoretical and practical approaches have suffered from many weaknesses. Coon’s main concern was to find human remains (Neanderthals in particular) rather than conducting clean archaeology excavations. On the other hand, his horrifyingly racist publications, rumors about his employment as an intelligence operative by the CIA during the WW II and the Cold War, plus countless unanswered questions concerning the sites he chose to excavate in Iran, all support this hypothesis that Archaeology was not his first priority in Iran.